CALCULATIONS OF OSCILLATOR STRENGTHS AND LIFETIMES OF CuI, AgI AND AuI USING COULOMB APPROXIMATION (Journal of Sciences, Islamic Republic of Iran)
Oscillator strengths and lifetimes of all energy levels of CuI, Agl and AuI were calculated using the Coulomb approximation (for The first time), and then compared with available data